2017
DOI: 10.1007/s00701-017-3317-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the clinical outcome of Vim radiosurgery with voxel-based morphometry: visual areas are linked with tremor arrest!

Abstract: Statistically significant structural changes in the relationship to clinical response after Vim RS are present in remote areas, advocating a distant neurobiological effect. The former regions are mainly involved in locomotor monitoring toward the local and distant environment, suggesting the recruiting requirement in targeting of the specific visuomotor networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 30 publications
3
25
0
Order By: Relevance
“…To co-ordinate the fine movements of patients with essential tremor with arm tremor, the brain needs to perform additional mechanisms of control and so the results of this study might represent adaptive reorganization and compensation through increased demands on the visuospatial control of skilled movements in patients with essential tremor. This view is supported by the findings of the study by Tuleasca et al that included a one-year follow-up of ventral intermediate nucleus (VIM) radiosurgery for essential tremor with voxel-based morphometry before and after treatment, which showed a significant change in gray matter volume in the left temporal pole and occipital cortex of the brain before and after treatment, resulting in the conclusion that visual areas might be linked with tremor arrest and be involved in the tremor loop [ 29 ].…”
Section: Discussionmentioning
confidence: 77%
“…To co-ordinate the fine movements of patients with essential tremor with arm tremor, the brain needs to perform additional mechanisms of control and so the results of this study might represent adaptive reorganization and compensation through increased demands on the visuospatial control of skilled movements in patients with essential tremor. This view is supported by the findings of the study by Tuleasca et al that included a one-year follow-up of ventral intermediate nucleus (VIM) radiosurgery for essential tremor with voxel-based morphometry before and after treatment, which showed a significant change in gray matter volume in the left temporal pole and occipital cortex of the brain before and after treatment, resulting in the conclusion that visual areas might be linked with tremor arrest and be involved in the tremor loop [ 29 ].…”
Section: Discussionmentioning
confidence: 77%
“…Here, we constructed a general linear model allowing predicting if an eventual pretherapeutic GMD in a specific anatomical area would relate to TSTH improvement. Of particular importance, we used TSTH as a continuous variable, without splitting of any group, as in the previous study [38]. We found that higher pretherapeutic GMD within right BA 18 predicted better TSTH improvement.…”
Section: Discussionmentioning
confidence: 92%
“…In a recently published paper [38], we have evaluated longitudinal GMD changes in time, between pretherapeutic state and 1 year after Vim RS. We assessed whether these structural MR changes would relate to TSTH improvement, by conventionally separating two different groups, clinically responders (<50% improvement) and non-responders (>=50% improvement).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of brain visual areas in tremor pathogenesis has been recently investigated by using a visual task of increasing difficulty to illustrate the impact of visuospatial network in tremor augmentation (Archer et al, 2018). Furthermore, recent series of investigations suggested that structural and functional changes of the visual cortex could be a preoperative predictor of optimum tremor outcome after ablative radiosurgery (Tuleasca et al, 2017(Tuleasca et al, , 2018b(Tuleasca et al, , 2018c.…”
Section: The Tremor Network and Pattern Of Beneficial Dbs Connectivitymentioning
confidence: 99%